Does the Added Worker Effect Matter? - Nezih Guner; Yuliya Kulikova; Arnau Valladares-Esteban (Institute of Labor Economics (IZA), 2020)
The added worker effect (AWE) measures the entry of individuals into the labor force due to their partners' job loss. We propose a new method to calculate the AWE, which allows us to estimate its effect on any labor market outcome. We show that the AWE reduces the fraction of households with two non-employed members. The AWE also accounts for why women's employment is less cyclical and more symmetric compared to men. In recessions, while some women lose their employment, others enter the labor market and find jobs. This keeps the female employment relatively stable.
Keywords: D1; E32; J21; J22; 330; household labor supply; intra-household insurance; female employment; cyclicality; skewness